Have a part in your kids’ lives and be engaged: parent-adolescent cell phone communication - Falcon Campos, Isaac Cruz Joel (Kansas State University, 2014)
Today more and more teenagers are adopting cell phone communication as the primary way to communicate with their peers and parents (Lenhart, Ling, Campbell, & Purcell, 2010). Literature is vast on the negative use of cell phones by teenagers such as sexting and bullying (e.g., Draper, 2012) and on the negative implications it has on them and their relationships with peers (e.g., D'Antona, Kevorkian & Russom, 2010). However, it is very limited in exploring how cell phone use affects parent-adolescent communication. To investigate this question, ten parent-adolescent dyads who have used cell phones for more than six months participated in 25-40 minute interviews consisting of 14 open-ended questions about how they use cell phones to communicate. The teenagers’ ages ranged from 14 to 18 years of age and the average age of the teenagers was 16.6 years. Transcripts of interviews were analyzed for main themes. I found that parents and teenagers text each other more than call each other. They use cell phones to communicate for practical reasons, such as safety/checking in with each other, as well as for relational reasons, such as staying in touch with each other at a distance and sharing fun information with each other. These devices help the parents and adolescents be available to each other, facilitate quick yet flexible response times, and allow parents to teach responsibility. However, they also face challenges of overuse, which can hinder parent-adolescent communication, and can lead to miscommunication. The results of this study can be used by Family Life Educators to help new parent and teen cell phone users to learn about the benefits of cell phones as well as some of the expected challenges and help them get the most out of their cell phone communication.
Keywords: Cell phone; Parent-adolescent; Communication; Teenagers; Mobile phones; Relationships; Adult Education (0516); Communication (0459); Individual & Family Studies (0628)